A Study Comparing the Knowledge, Surveillant and Preventive Behavior, and Control Behavior of Hand Foot Mouth Disease among Parents and Childcare Providers Living in High- and Low-epidemic Sub-districts: A Case Study in One District, Nakhon Ratchasima Province - Panarat, Wannapha; Hanklang, Suda; Patanasri, Kalaya (Nursing Science Journal of Thailand, 2022)
Purpose: To compare the differences of knowledge of disease, surveillant and preventive behavior, and control behavior of hand foot mouth disease among parents and child care providers in child development centers between a high-epidemic sub-district and a low-epidemic sub-district in Nakhon Ratchasima Province. Design: Descriptive research. Methods: Through random sampling, 65 and 64 parents of children in child care centers from high- and low-epidemic sub-districts for hand foot mouth disease, respectively, were recruited. All childcare providers from both sub-districts (n = 8, and n = 6, respectively) were also recruited. Data were collected using three questionnaires including knowledge, surveillant and preventive behavior, and control behavior of hand foot mouth disease. Independent sample t-test and Mann-Whitney U test were used for the data analysis. Main findings: The control behavior scores of parents in low-epidemic sub-district were significantly higher than those in high-epidemic sub-district (p < .05). Parents in both sub-districts had low knowledge and moderate surveillant and preventive behaviour, however, no significant differences were found. The knowledge about hand foot mouth disease scores of childcare providers in low-epidemic sub-district were significantly higher than those in high-epidemic sub-district (p < .01) while surveillant and preventive behavior as well as control behavior were not significantly different. Conclusions and recommendations: Parents from both sub-districts have low knowledge of hand foot mouth disease; thus, knowledge should be given every year, focusing on the causes, symptoms and spread of disease. Childcare providers should be strict with screening for the disease among children by using a flashlight to inspect and examine the oral cavity and checking the child's fever every morning before entering the centers. Local authorities should support health screening equipment and provide separate rooms for sick children in the child care centers.